High-intensity resistance training attenuates dexamethasone-induced muscle atrophy - Krug, André L. O. [UNESP]; Macedo, Anderson G. [UNESP]; Zago, Anderson S. [UNESP]; Rush, James W. E.; Santos, Carlos F.; Amaral, Sandra L. [UNESP] (Wiley-Blackwell, 2015)
We investigated the effects of high-intensity resistance training (RT) on dexamethasone (DEX) induced muscle atrophy in flexor hallucis longus (FHL), tibialis anterior (TA), and soleus (SOL) muscles. Rats underwent either high-intensity RT or were kept sedentary. In the last 10 days they received either DEX (0.5 mg/kg/d, i.p.) or saline. DEX reduced body weight (-21%), food intake (-28%), FHL and TA muscle mass (-20% and -18%), and increased in muscle-specific ring finger 1 (MuRF-1) protein level (+37% and +45.5%). RT attenuated FHL muscle atrophy by a combination of a low increase in MuRF-1 protein level (-3.5%) and significant increases in mammalian target of rapamycin (mTOR) (+63%) and p70S6K (+46% and +49% for Ctrl and DEX) protein levels. The data show that RT attenuated DEX-induced muscle atrophy by a combination of increases in mTOR and p70S6K protein level and a low increase in MuRF-1 protein level. This article is protected by copyright. All rights reserved.
Keywords: Glucocorticoids; Ladder climbing; Muscle atrophy; Resistance training; Skeletal muscle